Nutritional status, healthy lifestyle, and learning interest as predictors of physical fitness among high school students - Budi Gefri Ali; Damrah Damrah; Khairudin Khairudin; Wilda Welis (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aimed to determine the relationships between nutritional status, healthy lifestyle, and learning interest with physical fitness among students of SMA Negeri 1 Siberut Tengah, Mentawai Islands Regency. A quantitative correlational design was employed involving 114 students selected through proportional random sampling. Nutritional status was assessed using Body Mass Index (BMI), healthy lifestyle and learning interest were measured through questionnaires, and physical fitness was evaluated using the Indonesian Student Physical Fitness Test (TKSI). Data were analyzed using Pearson correlation and multiple regression analyses at a significance level of 0.05. The findings showed significant positive relationships between nutritional status and physical fitness (r = 0.454), healthy lifestyle and physical fitness (r = 0.550), and learning interest and physical fitness (r = 0.597). Simultaneously, nutritional status, healthy lifestyle, and learning interest significantly contributed to physical fitness (F = 13.699). Nutritional status, healthy lifestyle, and learning interest are important factors associated with students’ physical fitness. Improving these factors may enhance physical fitness and support students’ overall health and academic development.